JUDGE'S CONSIDERATION OF THE RECIPIENT'S CRIMINAL ACT BRIBERY FOR NEW STUDENT ADMISSIONS IN COLLEGE: (Study of Decision Number: 1/Pid.Sus-TPK/2023/PN Tjk) - Rafi'i, Muhammad Naufal (Hukum Responsif, 2026)
One of the main factors causing this corruption is the opportunities provided by parents or families who want their children or family members to graduate from a particular faculty or university. In the fierce competition for a place at a prestigious college, some parents feel depressed and anxious that the prestige of the family or the child's future depends on their success in gaining admission to the faculty of choice. The research method used is an empirical juridical approach, with data collected through field and literature studies. Data is processed through identification, classification, and compilation. The data analysis used is qualitative descriptive. The results of the study are: (1) The factors in the occurrence of criminal acts of bribery recipients in the admission of new students in higher education are the existence of greed factors, opportunity factors, need factors, and disclosure factors, which of these four factors does occur in the criminal act of accepting bribes in the admission of new students in higher education. (2) Then, in giving consideration, the judge analyzes three aspects to give a verdict based on justice, namely the juridical aspect, the philosophical aspect, and also the social aspect, where these three aspects are closely related in helping the judge to decide the case of the recipient of bribes in the admission of new students at state universities. The suggestion for all law enforcement officials and also state civil servants is to carry out their obligations and authority as they should without having to deviate from their positions and authority, as well as prioritizing justice in providing punishment for perpetrators of crimes that produce a deterrent effect for the perpetrators and prevent similar incidents in the future.